ADAMTS5 in Osteoarthritis: Biological Functions, Regulatory Network, and Potential Targeting Therapies - Jiang, Lejian; Lin, Jiachen; Zhao, Sen; Wu, Jiaqian; Jin, Yongming; Yu, Li; Wu, Nan; Wu, Zhihong; Wang, Yue; Lin, Mao (Frontiers in Molecular Biosciences, 2021)
ADAMTS5 is involved in the pathogenesis of OA. As the major aggrecanase-degrading articular cartilage matrix, ADAMTS5, has been regarded as a potential target for OA treatment. We here provide an updated insight on the regulation of ADAMTS5 and newly discovered therapeutic strategies for OA. Pathophysiological and molecular mechanisms underlying articular inflammation and mechanotransduction, as well as chondrocyte hypertrophy were discussed, and the role of ADAMTS5 in each biological process was reviewed, respectively. Senescence, inheritance, inflammation, and mechanical stress are involved in the overactivation of ADAMTS5, contributing to the pathogenesis of OA. Multiple molecular signaling pathways were observed to modulate ADAMTS5 expression, namely, Runx2, Fgf2, Notch, Wnt, NF-κB, YAP/TAZ, and the other inflammatory signaling pathways. Based on the fundamental understanding of ADAMTS5 in OA pathogenesis, monoclonal antibodies and small molecule inhibitors against ADAMTS5 were developed and proved to be beneficial pre-clinically both in vitro and in vivo. Recent novel RNA therapies demonstrated potentials in OA animal models. To sum up, ADAMTS5 inhibition and its signaling pathway–based modulations showed great potential in future therapeutic strategies for OA.